Brief Report: Immunization of HIV-Infected Adults in the UK With Haemophilus influenzae b/Meningococcal C Glycoconjugate and Pneumococcal Polysaccharide Vaccines. (1st November 2016) - MacLennan, Calman A.; Richter, Alex; Hodson, James; Faustini, Sian; Birtwistle, Jane; Whitelegg, Alison; Chigiga, Joyful; Singo, Mebie; Walker-Haywood, Jodie; Mulugeta, Betselot; Masuka, Sindiso; Mainey, Chris; et al.
Abstract : Abstract: U.K. guidelines for vaccinating HIV-infected adults against bacteria are based on limited data. We compared antibody responses between 211 HIV-infected and 73 HIV-uninfected adults vaccinated with pneumococcal polysaccharide vaccine (PPV) and Haemophilus influenzae b/meningococcal C polysaccharide-tetanus toxoid glycoconjugate vaccine (Hib/MenC-TT). IgG responses to Hib/MenC-TT were not significantly different. PPV induced median IgGs >1.3 μg/mL for 10/12 serotypes among HIV-uninfected participants and 5/12 in HIV-infected participants. HIV-uninfected adults had higher post-vaccination IgGs than HIV-infected adults for 4/12 serotypes ( P < 0.001). Responses did not associate with CD4 count or viral suppression. In a U.K. HIV-infected population, Hib/MenC-TT induced similar responses to HIV-uninfected adults, whereas PPV induced poor responses. Abstract : Supplemental Digital Content is Available in the Text.